Reconstruction of social cultural and educational environment in the context of professional stress: subjective experience o social pedagogues - Alifanovienė, Daiva; Šapelytė, Odeta; Kryukova, Tatyana (Social Welfare: Interdisciplinary Approach, 2016)
The paper deals with the social pedagogues’ subjective experience in the context of reconstruction of stress factors. The main aim is to reveal subjective experiences of social pedagogues from the aspect of stress factors they experience and how they express them in various social, cultural, and educational contexts. The respondents were chosen by target convenience sampling, i.e., social pedagogues (N=14), working at education and training institutions for at least two years of work experience; all having higher university education. To analyse the specialists’ experience a qualitative method of data collection have been chosen. Reconstructing a multi-layered context of social, cultural and educational diversity, a complex character of professional stress experienced by these specialists has been revealed. Evaluating the semantics of the chosen social pedagogues’ reactions to stress, overall stress harm to people, covering all layers of the personality structure manifests itself, and it can cause somatic and psychic complaints, social and professional maladaptation.
Keywords: coping with the stress; social pedagogues; individual experience